Supply chain and logistics issues of bio-energy production, Journal of Cleaner Production - Gold, Stefan; Seuring, Stefan (My University, 2011)
Within the concert of renewable energy technologies, bio-energy can play a decisive role during the next decades, when smartly designed and applied under favorable conditions. In this respect, efficient and effective supplychain and logistics management represent one key parameter. This paper presents a literature review of articles published in English-speaking peer-reviewed journals from 2000 to 2009, which cover the interface of bio-energyproduction and issues of logistics and supplychain management. First, the articles are assessed according to descriptive criteria such as journal, year of publication and research design applied. Then, issues and challenges of designing and operating biomass chains that secure stable and competitively-priced feedstock supply for bio-energy plants have been classified (1) into the operations harvesting and collection, storage, transport, and pre-treatment techniques as well as (2) into overall supply system design. Although biomass supplychains for energy use are manifold in terms of size, design, and functioning, most relevant issues regarding supplychain management and logistics of bio-energyproduction are identified. The findings are discussed against the backdrop of bio-energy as sustainable renewable energy option.
Keywords: Biomass; Bio-energy; Supplychain management; Logistics; Literature review